Integrating Computational Thinking into Islamic Religious Education: Developing Twenty-First Century Problem-Solving Competencies - Mahmoud Abdullah; Huzaiman Hushin; Salma Begum; Yousif Mahmadov; Abdallah El-Khatib (Al-Mukhlashin: Jurnal Multidisiplin Ilmu, 2026)
Computational Thinking (CT) has become an essential competency for students in the digital era. However, its integration into Islamic Religious Education has received little scholarly attention. This study aims to formulate a conceptual framework for integrating Computational Thinking into Islamic Religious Education while maintaining the integrity of Islamic values and pedagogical objectives. A mixed-method sequential explanatory design was employed. Quantitative data were collected from 328 students through competency assessments, while qualitative data were obtained through interviews with teachers and curriculum experts. The findings reveal that integrating decomposition, pattern recognition, abstraction, and algorithmic thinking into Islamic learning activities significantly enhances students’ analytical reasoning, decision-making abilities, and problem-solving competencies. Students also demonstrated greater capacity to apply Islamic teachings when addressing contemporary ethical and social issues. Teachers reported increased instructional innovation and higher classroom engagement. The novelty of this research lies in proposing the Islamic Computational Thinking Integration Framework, combining computational thinking competencies with Islamic ethical reasoning to prepare students for the challenges of Education 5.0.